A classification of isometry groups of homogeneous 3‐manifolds. Issue 13 (3rd February 2016) - Konstantis, Panagiotis; Loose, Frank
Abstract : We classify pairs ( M, G ) where M is a 3‐dimensional simply connected smooth manifold and G a Lie group acting on M transitively, effectively with compact isotropy group.